Diversity of echinoderms of class echinoidea and holothuroidea in waingapu old pier, east sumba regency - Ferdinand Ndawa Lu Remindima; Erfy Melany Lalupanda; Anita Tamu Ina (JPBIO (Jurnal Pendidikan Biologi), 2021)
Echinoderms are in habitats in coastal waters because  is a biota that can maintain the sustainability and  the balance of the coral reef ecosystem. Human activity  in utili zing Echinoderms, namely in Echinoidea  and Holothuroidea can affect life  his life. The purpose of this study was to determine the diversity of phyla  Echinoderms class Echinoidea and Holothuroidea at the Harbor  Waingapu Old Pier and its use as a medium  Biology learning. The research method used is  purposive sampling and analyzed using the approach  quantitative descriptive with the Shannon diversity index formula  Wiener. Echinoderm samples were calculated using the technique quadratic transects with a plot size of 2 x 2 meters are placed perpendicularly  in the direction of 50 meters using a plot of 30  plot. Environmental factors measured are temperature, salinity, degrees  acidity (pH) and levels of oxygen (DO). Measurements are taken  at each observation station. The results showed 11 species  Echinoderms are divided into 2 classes, namely Diadema setosum, Diadema savignyi, Tripneustes gratilla, Strongylocentrotus  droebachiensis, Echinocardium flavescens, Clypeaster subdepressus,  and Mespilia globulus from the class Echinoidea. Holothuria atra, Holothuria scraba, Euapta godeffroyi and Chiridota rigida from the class Holothuroidea. The diversity index obtained includes  medium category with a value of H = 1.696.